PENYELESAIAN WANPRESTASI OLEH AHLI WARIS DALAM PERJANJIAN KREDIT PADA USAHA EKONOMI DESA SIMPAN PINJAM AS SALAM DI DESA TANJUNG PUNAK KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Agus Kusni Mubarok; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In Article 1100 of the Civil Code it is affirmed, "the heirs who have been willing to receive an inheritance, must take part in the payment of debts, will and other burdens, in proportion to what each of them receives from the inheritance. Related to the obligations of the heirs to pay debts. the inheritor, based on Article 1101 of the Civil Code stipulates that the obligation to pay is borne individually, each according to the amount of his inheritance, without reducing the rights of the creditor to all inheritance, as long as the inheritance has not been divided, and without reducing the rights of the creditors. . Article 833 paragraph (1) of the Civil Code stipulates that an heir automatically, due to the law, obtains property rights over all property, rights and all debts from the heir. Therefore the researcher took the title Settlement of Default Against Inheritance in a Credit Agreement on the Economic Business of the As Salam Savings and Loan Village in Tanjung Punak Village, Rupat Utara District, Bengkalis Regency.The purpose of this study is to determine the settlement of default disputes against the heirs in a credit agreement with fiduciary guarantees for village economic enterprises in Tanjung Punak village, Rupat Utara sub-district, Bengkalis district and to find out what efforts can be made by village economic enterprises if the heirs are unable to pay their debts. Because in this study the author directly conducted research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in the village of Tanjung Punak, Rupat Utara District, Bengkalis Regency. While the population and samples are the head of the village of Tanjung Punak, the head of UED-SP As-Salam and the heirs. The type of research in this thesis is sociological law research.The conclusions obtained from the research results are First The position of the heir in the case that the author examines as the successor of the debt that is inherited to him so that he has a position as a debtor in this case,Second Efforts that can be made by village economic enterprises if the heirs are unable to pay their debts is to seek relief in installment payments, the given the opportunity to pay installments in an amount smaller than what it should be, the provision of partial debt repayment opportunities, the heirs can pay a portion of the total debt and Underhand collateral sales are made so that the heirs are still given the opportunity to offer / sell their own collateral to do so. full payment of debt payments.Keywords: Default, Heirs, Credit Agreement, Usaha Ekonomi Desa-Simpan Pinjam